Comparative analysis of instantaneous wave-free ratio and quantitative real-time myocardial contrast echocardiography for the assessment of myocardial perfusion - Liang, Li; Zhu, Yongxiang; Li, Fangfang; Guo, Kai; Chang, Shang; Li, Qian; Zhang, Yaojun; Li, Dongye (Frontiers in Cardiovascular Medicine, 2022)
Background and Hypothesis: The field of coronary artery physiology is developing rapidly and changing the practice of interventional cardiology. A new functional evaluation technique using instantaneous wave-free ratio (iFR) has become an alternative to fractional flow reserve. Future research studies need to determine whether physiological indicators play a role in evaluating myocardial perfusion in the catheter room. Methods: Thirty-eight patients scheduled for coronary angiography and iFR evaluation underwent a real-time myocardial contrast echocardiography (RT-MCE) examination at rest. The myocardial perfusion parameters (A, β, and A×β) on the myocardial perfusion curve were quantitatively analyzed using Q-Lab software. Coronary angiography and iFR assessment were completed within one week after RT-MCE examination in all patients. Correlation analysis was used to identify iFR- and MCE-related indicators. The sensitivity and specificity of iFR in quantitative detection of coronary microcirculation were obtained. Results: The correlation coefficients between iFR and A, β, and A×β were 0.81, 0.66, and 0.82, respectively. The cutoff value for iFR was 0.85 for microvascular ischemia detection, while the sensitivity and specificity for diagnosis of myocardial perfusion were 90.7% and 89.9%, respectively. The receiver operating characteristic (ROC) curve area for iFR was 0.946 in the segments related to myocardial blood flow. Conclusions: The iFR is an effective tool for detecting myocardial microcirculation perfusion, with satisfactory diagnostic performance and a demonstrated role in physiological indices used for the perfusion assessment.